Forensic Medicine: textbook - Пиголкин, Ю. И. судебно-медицинская экспертиза 19520323 Юрий Иванович (Textbook, 2019)
The textbook outlines the main provisions of forensic medicine in accordance with the syllabus for the course of Forensic medicine at higher professional education establishments, and an innovative modular educational program. The textbook captures the current achievements of forensic medicine in areas of forensic traumatology, tanatology and person?s identification. All information is presented in the form of a system of interconnected modules, with consideration to the Bologna Declaration, latest updates in legislation and new regulations on determining the severity of harm to human health. The textbook can provide invaluable assistance to students in obtaining theoretical knowledge and mastering practical skills for further work in the field of forensic medicine.